SPASIAL INDEKS KEKERINGAN DAERAH ALIRAN SUNGAI INDRAGIRI BERDASARKAN TEORI RUN - Nahar Afrizal; Manyuk Fauzi; Imam Suprayogi (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
The impact of drought, in addition to reduced availability and supply of water, also decreased food production, and land / forest fires. Drought provides an opportunity for serious forest fires to occur in various forest areas in Indonesia. Because of this, the drought index analysis was carried out in the Indragiri watershed in Riau Province. The drought index is analyzed using the Run Theory method. Limitations of observation station data in the Indragiri watershed, satellite data is used which is managed by The National Centers for Environmental Prediction (NCEP) from 1984 to 2013. The Run Theory method can be used to spatially analyze drought that occurs in drought that occurs in Indragiri watershed. Based on the results of the analysis of the drought index, the highest percentage of drought index occurred in 1984 with a value of 87.49% (normal classification), while the lowest percentage of drought index occurred in 1994 with a value of 61.68% (very dry classification).